2008
DOI: 10.1080/00365590802025857
|View full text |Cite
|
Sign up to set email alerts
|

Increasing numbers of ureteric injuries after the introduction of laparoscopic surgery

Abstract: Iatrogenic ureteric injuries have increased markedly during the past two decades. Gynaecological laparoscopic procedures account for more than half of the injuries, and the most common location is the lower ureter. Most injuries are treated by ureteroneocystostomy, but endourological treatment yields acceptable results. To improve the management of ureteric injury there must be a high index of suspicion, especially during laparoscopic operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 19 publications
(27 reference statements)
4
84
3
2
Order By: Relevance
“…It has been reported that iatrogenic ureteral injuries in laparoscopic surgery are less frequently discovered intraoperatively compared with open surgery [22]. Our study does not confirm this observation.…”
Section: Discussioncontrasting
confidence: 70%
“…It has been reported that iatrogenic ureteral injuries in laparoscopic surgery are less frequently discovered intraoperatively compared with open surgery [22]. Our study does not confirm this observation.…”
Section: Discussioncontrasting
confidence: 70%
“…The literature data regarding this issue is conflicting. In some studies, the highest incidence has been found with abdominal hysterectomies (17,18), but others reported a higher incidence with laparoscopic hysterectomies (19,20). In contrast, in a prospective study by Ibeanu et al (7), the authors reported that the vaginal hysterectomy was associated with more ureteric injuries (2.6%) than abdominal (1.7%) and laparoscopically assisted vaginal hysterectomies (0%), in accordance with our experience.…”
Section: Discussioncontrasting
confidence: 48%
“…Endometriosis rarely involves the upper urinary tract, (1-2 % of all cases of stenosis), 84 % of which are associated with concomitant bladder involvement [3,4]. The incidence of iatrogenic ureteral injury ranges between 0.1 % and 2.5 % of all the surgical procedures [5,6]; during recent years, an increasing incidence of iatrogenic strictures has been observed, due to the widespread diffusion of abdominal and gynaecological laparoscopic surgery and upper urinary tract endoscopy [7].…”
Section: Introductionmentioning
confidence: 99%